2014
DOI: 10.1186/cc13818
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the impact of serial troponin measurements on the diagnosis of myocardial infarction and hospital and six-month mortality in patients admitted to ICU with non-cardiac diagnoses

Abstract: IntroductionTroponin T (cTnT) elevation is common in patients in the Intensive Care Unit (ICU) and associated with morbidity and mortality. Our aim was to determine the epidemiology of raised cTnT levels and contemporaneous electrocardiogram (ECG) changes suggesting myocardial infarction (MI) in ICU patients admitted for non-cardiac reasons.MethodscTnT and ECGs were recorded daily during week 1 and on alternate days during week 2 until discharge from ICU or death. ECGs were interpreted independently for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 28 publications
4
48
0
2
Order By: Relevance
“…It can be concluded that troponin levels were higher among patients who died compared to live group. 17 Even though it was found that troponin T levels were significantly high among the mortality group, it was not statistically significant: p=0.56, 0.84 and 0.67 on day 1, 3 and 5 respectively. It's proved here that in the outcome of patients in relation to high and normal troponin T levels, among patients with high troponin T levels, 82.4% it accounted to mortality.…”
Section: Discussionmentioning
confidence: 92%
“…It can be concluded that troponin levels were higher among patients who died compared to live group. 17 Even though it was found that troponin T levels were significantly high among the mortality group, it was not statistically significant: p=0.56, 0.84 and 0.67 on day 1, 3 and 5 respectively. It's proved here that in the outcome of patients in relation to high and normal troponin T levels, among patients with high troponin T levels, 82.4% it accounted to mortality.…”
Section: Discussionmentioning
confidence: 92%
“…Coronary oxygen supplydemand imbalance may result in ''type II'' myocardial infarction or injury. Troponin release is prevalent in the critically ill and is associated with higher mortality [4,5].…”
Section: Physiological Arguments Against a Blanket Restrictive Hb Trimentioning
confidence: 99%
“…Evidence is also limited by the under-representation of patients with CVD in trials. Observational studies suggest the prevalence of CVD in ICU patients is around 30% [1,3]; however patients with CVD accounted for only 20% of patients recruited to the Transfusion Requirements in Critical Care (TRICC) trial compared with 29% of patients excluded [9], and only 14% of patients recruited to the Transfusion Requirements in Septic Shock (TRISS) trial [11]. A trial undertaken in patients presenting with acute gastrointestinal bleeding trial excluded all patients with significant CVD [12].…”
Section: Evidence From Transfusion Trialsmentioning
confidence: 99%
“…EKGs are not performed routinely and there is significant interobserver variability [35]. Troponin release is prevalent in the critically ill [1,36] and there are multiple causes. Potential cardiac mechanisms include increased thrombogenicity leading to coronary plaque rupture and thrombosis (type I myocardial infarction) or underlying critical coronary artery disease leading to an oxygen supply/demand imbalance (type II myocardial infarction) [34].…”
Section: Acute Coronary Syndromementioning
confidence: 99%